Physiological Alterations in Deletion Mutants of Two Insulin-Like Peptides Encoded in Maruca vitrata Using CRISPR/Cas9 - Al Baki, Md. Abdullah; Kyo Jung, Jin; Kim, Yonggyun (Frontiers in Physiology, 2021)
Most insect species encode multiple insulin-like peptides (ILPs) that exhibit functional overlaps in mediating physiological processes such as development and reproduction. Why do they need multiple ILPs? To address this question, we tested a hypothesis of the requirement of multiple ILPs by generating mutants lacking individual ILP genes using the CRISPR/Cas9 technology. Two ILPs (ILP1 and ILP2) in the legume pod borer, Maruca vitrata, mediate similar physiological processes such as hemolymph sugar level, larval development, and adult reproduction. Individual knock-out mutants (ΔILP1 and ΔILP2) were generated. They showed successful development from larvae to adults. However, they suffered from high hemolymph sugar levels by enhancing trehalose titers in the hemolymph. The hyperglycemic effect was more evident in ΔILP2 mutants than in ΔILP1 mutants. Both mutants showed increased expression of trehalose-6-phosphate synthase but suppressed expression of trehalase. These mutants also showed altered expression patterns of insulin signaling components. Expression levels of insulin receptor and Akt genes were upregulated, while those of FOXO and Target of rapamycin genes were downregulated in these mutants. These alterations of signal components resulted in significant retardation of immature development and reduced body sizes. ΔILP1 or ΔILP2 females exhibited poor oocyte development. Bromo-uridine incorporation was much reduced at the germarium of ovarioles of these mutants compared with wild females. Expression of the vitellogenin gene was also reduced in these mutants. Furthermore, males of these deletion mutants showed impaired reproductive activities when they mated with wild-type females. These results suggest that both ILPs are required for mediating larval development and adult reproduction in M. vitrata.